ADAPTATION OF THE OBTAINED in vitro Gentiana lutea L. PLANTS TO ex vitro AND in situ CONDITIONS - О. Yu.; L. R.; N. М. (Biotechnologia Acta, 2015)
The objective of the research was to develop the technology of introduction of the obtained by microclonal propagation Gentiana lutea L. plants into conditions in situ. Methods of cultivation of plant objects in vitro were used. There were chosen optimal conditions for rooting G. lutea shoots obtained through microclonal propagation in vitro: МS/2 medium with twice decreased concentration of NH4NO3 without vitamins and sucrose supplemented with 3 g/l of mannite and 0.05 mg/l kinetin, and agar (4 mg/l) in combination with perlite (16 g/l) used as a maintaining substrate; or the nutrient medium (MS/2 without vitamins and smaller concentration of N4NO3) with gradual decrease of carbohydrates from 10 g/l to 2 g/l, and further rooting experimental shoots in tap water. Rooted plants were adapted to conditions ex vitro through planting them into flowerpots with soil and gradual changing hothouse regime for exposed one. The share of adapted to in situ conditions plants (21% after a year of planting) proves the suggested method to be efficient and promising. There was suggested this technology is the most efficient ones for revival of disturbed G. lutea populations that includes repatriation of rooted and adapted to ex vitro conditions plants obtained through microclonal propagation in vitro.